Original data field testing of aggregation-sex pheromone for longhorn beetles Aromia moschata moschata and Holopleura marginata (Cerambycidae) - Aggregation-sex pheromone field trapping data for Aromia moschata moschata and Holopleura marginata - Larsson, Mattias; Millar, Jocelyn (Swedish University of Agricultural Sciences, 2022)
Original data for Molander et al: p-Mentha-1,3-dien-9-ol: A novel aggregation-sex pheromone for monitoring longhorn beetles (Cerambycidae) in Eurasia and North America

Longhorn beetles (Cerambycidae) are a diverse family of beetles with considerable impact as forest pests and vectors of pathogens, as well as being important components of forest food webs and ecosystem functionality. In recent years, numerous cerambycid pheromones have been identified, revealing some broad general patterns in functionality in terms of sex or aggregation- sex pheromones in different subfamilies, and different types of compounds characterizing the pheromones of various cerambycid taxa. Here, we include supplementary and original data regarding the identification of the aggregation- sex pheromones of the Eurasian longhorn beetle Aromia moschata moschata (L.) (Cerambycinae; tribe Callichromatini) and the North American species Holopleura marginata LeConte (Cerambycinae; Holopleurini). This is part of an ongoing effort to extend the taxonomic coverage of identified cerambycid pheromones, and to expand the prospects for cerambycid monitoring into the study of biodiversity and ecosystem services. Both species were found to use the novel pheromone compound p-mentha-1,3-dien-9-ol, which also attracted significant numbers of the longhorn beetle Xestoleptura crassipes (LeConte) (Lepturinae; Lepturini) in trials in California. p-Mentha-1,3-dien-9-ol represents a class of pheromone compounds novel to both tribes (Callichromatini and Holopleurini), further increasing the chemical space of identified pheromones within the subfamily Cerambycinae. This compound is also noteworthy because it represents an entirely different chemical class of pheromones than the monoepoxide (E)-2-cis-6,7-epoxynonenal previously reported as an aggregation-sex pheromone for the invasive Asian congener Aromia bungii (Faldermann).

Original data from field trapping studies of catches of different species to different lures tested in the study.

Aromia moschata trapping: Field trapping trials were performed at Revingehed near Lake Krankesjön, at 20 different field trapping sites (replicates) identified only by numbers 1-20. Treatments compared comprised two different baits: Dienol (p-Mentha-1,3-dien-9-ol dissolved in isopropanol) and Control (isopropanol only).
Table columns: Year, Set date, Emptying date, Ordinal date, Trap site, Treatment (Dienol or Control), Total catch, Catch males, Catch females.

Holopleura marginata trapping (and other species): Field trapping trials were performed at four different sites in northern California: 1) Slaughterhouse Ravine, Magalia, Butte Co. (Magalia), 2) Rattlesnake Creek at Forest Road 27N12 (Rattle), 3) Junction Forest Roads 27N06 and 27N12Y (Rd27), 4) Whispering Pines Pet Clinic property, Magalia, Butte Co. (Whisp). Treatments compared comprised four different bait types with active components dissolved in isopropanol: Dienol (p-Mentha-1,3-dien-9-ol), Alcohol (2-(4-methylphenyl)-1-propanol = p-cymen-9-ol), 1:1 blend of the former, and Control (isopropanol).

Originaldata för Molander m. fl: p-Mentha-1,3-dien-9-ol: A novel aggregation-sex pheromone for monitoring longhorn beetles (Cerambycidae) in Eurasia and North America

Långhorningsskalbaggar (Cerambycidae) är en mångformig familj av skalbaggar av väsentlig betydelse som skogsskadegörare och sjukdomsvektorer, och är också viktiga komponenter i skogens näringsvävar och ekosystemets funktionalitet. Under senare år har många olika långhorningsferomoner identifierats, vilket har visat storskaliga generella mönster i deras funktionalitet som sex- eller aggregation-sex-feromoner i olika underfamiljer, och vilka olika typer av ämnen som kännetecknar feromonerna i olika cerambycid-taxa. Här inkluderar vi kompletterande och originaldata för identifieringar av aggregation-sex-feromoner för den eurasiska långhorningen Aromia moschata moschata (L.) (Cerambycinae; tribus Callichromatini) och den nordamerikanska arten Holopleura marginata LeConte (Cerambycinae; tribus Holopleurini). Detta är en del av pågående arbete med att utöka den taxonomiska täckningen av identifierade cerambycidferomoner, och bredda möjligheterna för övervakning av långhorningar för studier av biologisk mångfald och ekosystemtjänster. Båda arterna befanns producera den nya feromonsubstansen p-mentha-1,3-dien-9-ol, som också attraherade signifikanta antal av långhorningen Xestoleptura crassipes (LeConte) (Lepturinae; Lepturini) i studier i Kalifornien. p-Mentha-1,3-dien-9-ol utgör en grupp av feromonsubstanser som är ny för båda dessa tribes (Callichromatini and Holopleurini), vilket ytterligare ökar diversiteten av identifierade feromoner inom underfamiljen Cerambycinae. Detta ämne är också intressant därför att det utgör en helt ny kemisk grupp av feromoner än monoepoxiden (E)-2-cis-6,7-epoxynonenal, som tidigare har rapporterats som ett aggregation-sex-feromon för den invasiva asiatiska långhorningen Aromia bungii (Faldermann).

Originaldata från fällstudier av fångster av olika arter till olika beten som testats i studien.

Aromia moschata-fångster: Fångstförsöken utfördes på Revingehed nära Krankesjön, på 20 olika fällplatser (replikat) endast identifierade med nummer från 1-20. Behandlingar som jämfördes utgjordes av två olika betestyper: Dienol (p-Mentha-1,3-dien-9-ol löst i isopropanol) respektive Kontroll (endast isopropanol).
Tabellkolumner: År, Uppsättningsdatum, Tömningsdatum, Ordinaldatum, Fällplats, Behandling (Dienol eller Kontroll), Totalfångst, Fångst hanar, Fångst honor.

Holopleura marginata-fångster (och andra arter): Fångstförsöken utfördes på fyra olika platser i norra Kalifornien: 1) Slaughterhouse Ravine, Magalia, Butte Co. (Magalia), 2) Rattlesnake Creek at Forest Road 27N12 (Rattle), 3) Junction Forest Roads 27N06 and 27N12Y (Rd27), 4) Whispering Pines Pet Clinic property, Magalia, Butte Co. (Whisp). Behandlingar som jämfördes utgjordes av fyra olika betestyper med aktiva substanser lösta i isopropanol: Dienol (p-Mentha-1,3-dien-9-ol), Alcohol (2-(4-methylphenyl)-1-propanol = p-cymen-9-ol), 1:1-blandning av föregående, samt Kontroll (isopropanol).
Tabellkolumner: Fångstplats, Artkod, Datum, Ordinaldatum, Totalfångst, Dienol-fångst, Alkohol-fångst, Fångst till 1:1-blandning, Kontrollfångst, Fångst Släkte, Fångst art, Noteringar.
Originaldata fälttester av aggreggationsferomon för långhorningsskalbaggar Aromia moschata moschata och Holopleura marginata - Aggregation-sexferomon fällfångstdata för Aromia moschata moschata och Holopleura marginata
Keywords: pheromones; feromoner; Chemical identification; Kemisk identifiering; Biodiversity monitoring; Biodiversitet övervakning; Natural Sciences; Naturvetenskap; Analytical Chemistry; Analytisk kemi; Biological Sciences; Biologi; Zoology; Zoologi; Ecology; Ekologi; Biota; Biologi och ekologi